Percutaneous Hamstring Lengthening Surgery is as Effective as Open Lengthening in Children With Cerebral Palsy. Issue 7 (August 2019) - Nazareth, Alexander; Rethlefsen, Susan; Sousa, Ted C.; Mueske, Nicole M.; Wren, Tishya A.L.; Kay, Robert M.
Abstract : Background: Surgical lengthening of the hamstrings is often performed to correct crouch gait in children with cerebral palsy (CP). Previous studies have demonstrated the effectiveness of open hamstring lengthening (oHSL) in improving knee extension static and dynamic range of motion; however, literature regarding percutaneous hamstring lengthening (pHSL) is limited. The purpose of this study was to investigate the effect of open versus pHSL for improving crouch gait and knee function in children with CP. Methods: This retrospective cohort study included 87 ambulatory children with CP who underwent HLS surgery with both preoperative and postoperative gait analysis (mean time, 29.4±19.9 mo after surgery) testing between 1997 and 2015. In total, 65 patients underwent oHLS surgery (mean age, 8.5±2.5 y) and 22 patients underwent pHSL surgery (mean age, 8.3±2.3 y). Lower extremity three-dimensional kinematic data were collected while subjects walked at a self-selected speed. Outcome variables for operative limbs were compared within and between groups using t tests, χ 2 tests, and multiple regression analysis. Results: Significant postoperative decreases in knee flexion at initial contact were seen for both open (Δ12.7±13.4 degrees; P <0.001) and percutaneous (Δ19.1±13.1 degrees; P <0.001) groups. Increased postoperative maximum knee extension in stance was found for both open (Δ8.2±16.8 degrees; P =0.001) and percutaneous (Δ14.4±16.5 degrees; P =0.001) groups. No significant differences between open and percutaneous groups were found when comparing postoperative changes in kinematic variables between groups after adjusting for covariates. Postoperative changes in static range of motion were similar between lengthening groups. Conclusions: pHSL is as effective as open lengthening in improving stance phase knee kinematics during gait in children with CP. This is the first study to compare the kinematic effects of open versus pHSL in the pediatric population. Percutaneous lengthening is tolerated well by patients, and as it allows for rapid rehabilitation it may be preferable to the open procedure. Level of Evidence: Level III—retrospective comparative study.